2016
DOI: 10.1017/s0376892916000035
|View full text |Cite
|
Sign up to set email alerts
|

From self-subsistence farm production to khat: driving forces of change in Ethiopian agroforestry homegardens

Abstract: SUMMARYTraditional agroforestry homegardens deliver multiple products and benefits, including food security and livelihoods for rural households in Ethiopia. However, this land use has been changing towards monoculture production of khat (Catha edulis). This study analyses the development trajectories and causes of change in agroforestry homegardens. In total, 84 interviews, including key informant and semi-structured household interviews, and eight focus group discussions were conducted in the Southern Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 30 publications
4
24
0
Order By: Relevance
“…Multiple provisioning services (wood, dairy products, and food crops, including vegetables and fruits) provided by agroforestry homegardens are important for household nutrition, income, and food security [71][72][73][74], which helps farmers to diversify their household production and financial income [75]. Furthermore, the growing number of coffee kiosks in villages and towns that are supported by small-scale traders, mainly women, indicates the importance of coffee as a traditional cash crop for the viability of rural settlements' practicing traditional agroforestry at the local level, as well as for consumers at multiple levels [17].…”
Section: Land Management Strategies To Maintain Priority Land Coversmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple provisioning services (wood, dairy products, and food crops, including vegetables and fruits) provided by agroforestry homegardens are important for household nutrition, income, and food security [71][72][73][74], which helps farmers to diversify their household production and financial income [75]. Furthermore, the growing number of coffee kiosks in villages and towns that are supported by small-scale traders, mainly women, indicates the importance of coffee as a traditional cash crop for the viability of rural settlements' practicing traditional agroforestry at the local level, as well as for consumers at multiple levels [17].…”
Section: Land Management Strategies To Maintain Priority Land Coversmentioning
confidence: 99%
“…Nevertheless, most traditional agroforestry practices in developing countries, including Ethiopia, are threatened by unsustainable land management [85,86]. The deterioration of traditional agroforestry landscapes is driven by population pressure, declining farm size, the global market, and socio-economic changes in society [17,58,70,74,77,87]. The introduction and integration of high-yield crops to increase farm productivity, the improvement of value-added production from food and traditional cash crops, and the creation of opportunities for off-farm employment to support the increasing population of landless farmers are essential [61,88].…”
Section: Land Management Strategies To Maintain Priority Land Coversmentioning
confidence: 99%
“…Drought, combined with highly variable access to a high-quality natural resource base and increasing costs of food and services, pushes farmers to explore a variety of mitigating and adaptive strategies (Dar and Twomlow 2007;Davis et al 2012;Hounkonnou et al 2012). To compound these drivers of insecurity, farmers must also deal with the added pressures of population-induced land fragmentation and redistribution (Feed the Future 2013; Gebrehiwot et al 2016;Hounkonnou et al 2012). All land is property of the Ethiopian government, which redistributes land and determines plot size in part by family size.…”
Section: Khat In a Community Resilience Frameworkmentioning
confidence: 99%
“…In many cases the difference between a productive plot and a degraded plot is only a few meters (interview with Productive Safety Net Programme [PSNP, a government-operated insurance program to guard against food insecurity among smallholders] personnel, January 24, 2015). Previous studies have found that in response to land fragmentation farmers seek out khat to improve economic capacity, despite smaller productive capacity (Gebrehiwot et al 2016).…”
Section: Khat In a Community Resilience Frameworkmentioning
confidence: 99%
See 1 more Smart Citation